PERANCANGAN SISTEM PENGAJUAN SURAT KETERANGAN TERDAFTAR BAGI KELOMPOK MASYARAKAT BERBASIS WEB DI BAGIAN KESEJAHTERAAN MASYARAKAT SEKRETARIAT PEMERINTAH KABUPATEN BANYUWANGI - Nurdiana Fitri Arifah; Abd. Ghofur; Ahmad Mulyadi (Jurnal Riset Sistem Informasi, 2025)
This project aims to develop a web-based solution that simplifies the submission of POKMAS certification letters for Muslim Communities under the Departement of Social Affairs (Kesra) of Banyuwangi Regency. The system is designed to enhance accessibility, speed up the process, and improve transparency from the application to the approval stage. By using modern technology, the development of this system aims to improve performance and user comfort. The community can submit applications online, which will then be processed by Kesra Banyuwangi through a more efficient an structured workflow. Previously, the submission of certification letters often took a long time and involved many manual steps, but with this system, the process becomes faster and clearer. Additionally, the system provides automatic notifications to both applicants an officers, minimizing delays or oversights. As a result, the manual workload is reduced, and administrative services become faster and more convenient. The system also allows for real-time tracking of application statuses, providing certainty for the public an increasing trust in the services provided. Furthermore, the system can generate periodic reports that help Kesra in evaluating an improving services. Ultimately, this sytem not only makes it easier for the community to access services but also enhances the overall operational efficiency of Kesra Banyuwangi administration.